Relationship between Beliefs of Teachers about and Their Use of Explicit Instruction When Fostering Students' Scientific Inquiry Competencies - Verena Petermann; Andreas Vorholzer (MDPI AG, 2022)
An efficient approach to fostering students' scientific inquiry (SI) competencies (e.g., planning investigations) is to combine student engagement in inquiry activities with explicit instruction that addresses corresponding concepts (e.g., the control-of-variables strategy). Despite its effectiveness, explicit instruction on SI-related concepts seems to be rarely employed in science classrooms. As a vital component of professional competence, teachers' beliefs are a potential cause for the rare use of explicit instruction. The aim of this study is to investigate the relationship between teachers' beliefs about the usefulness of explicit instruction as well as their own abilities and teacher performance. In a mixed method approach, the beliefs of N = 16 teachers were captured with a questionnaire, while their teaching practice was approximated through a combination of a lesson planning task and a semi-structured interview. Analyses of response patterns, a qualitative content analysis of the planned lessons, and correlation analyses were used to investigate the relationship between beliefs and performance. The findings suggest that beliefs about the usefulness of explicit instruction for fostering SI competencies may be a necessary but not a sufficient condition for its implementation. Furthermore, the results suggest the importance of assessing and investigating teachers' beliefs on a goal-specific level.